Comparative evaluation of bioactivity of MTA plus and MTA plus chitosan conjugate in phosphate buffer saline an invitro study - Geeta Hiremath; Shreshtha Pramanik; Priya Horatti; Anil (Saudi Dental Journal)
Background and Objective: Various materials like MTA, Biodentine etc have been used for the regeneration of lost dental tissues. Still, the quest for newer materials to enhance the bioactivity of the existing materials continues. Hence this study aims at the evaluation of bioactivity of MTA Plus when conjugated with Chitosan in phosphate buffer saline. Methodology: Materials used were MTA Plus (Group 1), MTA Plus and chitosan conjugate(Group 2). The materials were mixed and placed in phosphate buffer saline. Bioactivity of Group 1 and Group 2 materials were assessed at 7 days and 28 day’s time intervals using SEM-EDX analysis. Results: SEM analysis of group 1 revealed a compact and agglomerate lath-like appearance with uniform particle size. SEM analysis of group 2 reveals acicular and lath-like appearance of the precipitate on the material surface. EDX analysis of the freshly prepared materials gave the qualitative semiquantitative elemental composition on the material surfaces after immersion in PBS for 7 and 28 days. Conclusion: MTA Plus Chitosan conjugate had greater potential to form apatite crystals on its surface. Hence, Chitosan can be used as a vehicle for the currently available materials to enhance the bioactivity and fasten the healing process.